Clinical Implementation of 7T MRI for the Identification of Incidental Intracranial Aneurysms versus Anatomic Variants - Radojewski, P.; Slotboom, J.; Joseph, A.; Wiest, R.; Mordasini, P. (American Journal of Neuroradiology, 2021)
SUMMARY: Most unruptured intracranial aneurysms can be adequately characterized using 1.5T and 3T MR imaging. Findings in a subgroup of patients can remain unclear due to difficulties in distinguishing aneurysms from vascular anatomic variants. We retrospectively analyzed clinical data from 30 patients with suspected incidental aneurysms on 3T MR imaging who underwent 7T MR imaging. In all 30 cases, the differentiation of an aneurysm versus a vascular variant could be achieved. In 20 cases (66%), the initial suspected diagnosis was revised. Our findings suggest that 7T MR imaging provides a clarification tool for the group of patients with suspected unruptured intracranial aneurysms and diagnostic ambiguity after standard 3T MR imaging.UIAunruptured intracranial aneurysm